Interventions for preventing falls in people with multiple sclerosis - Hayes, Sara (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The aim of this review is to evaluate the effectiveness of interventions designed to reduce the rate of falls in people with multiple sclerosis (MS). Specific objectives include comparing the effectiveness of single, multiple and multifactorial interventions designed to reduce the rate of falls in people with MS.